Education and Supplementary Food Provision for Tuberculosis Patients at the Merdeka Health Center, Palembang City - Emma Novita Emma; Iche Andriyani Liberty; Mariana; Pariyana; Hanna Marsinta Uli; Afrida Yolanda Putri; Syafira Nofwanda (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
The nutritional status of TB patients is very important because it is a simple clinical sign to see the success of TB therapy. Health education or counseling is one way to change a person's knowledge and attitudes about health and can indirectly affect nutritional status. The assessment method for community service is carried out using lecture and discussion methods. Community service will be held on November 3, 2021, at the Merdeka Health Center in Palembang. The population of this activity is TB patients and drug-taking supervisors (PMO) in the working area of the Merdeka Palembang Health Center. The number of participants is 22 people. The evaluation was carried out by conducting pre-test and post-test to assess the increase in knowledge before and after education/counseling about nutrition in TB patients. The results of community service activities showed that the provision of education significantly affected the knowledge of the nutritional status of patients (p-value <0.05) between patients before being given education and after being given education. Suggestions that can be given are the need for knowledge about the nutrition and diet of TB patients to improve their nutritional status so that treatment can be optimal.